2013
DOI: 10.1002/pbc.24864
|View full text |Cite
|
Sign up to set email alerts
|

Use of a clinical pathway to improve the acute management of vaso‐occlusive crisis pain in pediatric sickle cell disease

Abstract: The use of a clinical pathway for sickle cell VOC in the PED can improve important aspects of pain management and merits further investigation and implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 30 publications
3
31
1
Order By: Relevance
“…Our post‐intervention admission rate of 41% is lower that what has been previously reported in the literature. Previous studies of VOC in children have reported admission rates between 50 and 78% . We estimate that 49 admissions and 307 inpatient days are avoided annually through the initiative.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our post‐intervention admission rate of 41% is lower that what has been previously reported in the literature. Previous studies of VOC in children have reported admission rates between 50 and 78% . We estimate that 49 admissions and 307 inpatient days are avoided annually through the initiative.…”
Section: Discussionmentioning
confidence: 97%
“…We found the high admission rates for patients presenting with VOC both locally (50–57%) and nationally (50–78%) to be unacceptable. At our center, we observed an inconsistent approach to pain management both in the ED and after admission.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A third concern for frequent NSAID use is that some pediatric SCD patients have CYP2C9 allele variants that alter NSAID metabolism and may place these patients at increased risk for NSAID toxicity [34]. A final issue relevant to inducing AKI is that ER and inpatient teams may initially manage patients with ketorolac as part of standardized clinical pain pathways or based on individual physician preference [35, 36]. Two randomized clinical trials failed to demonstrate that ketorolac can reduce hospital days, or total morphine dose [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were age less than 18 years or chief complaint unrelated to VOEs in patients with SCD. The patient sample size was estimated by data abstraction from a prior study27 using the following assumptions: μ (0) = 293 “known” mean value for SCD population; μ (1) = 236 “expected” mean” value from sample; σ (standard deviation) = 154 for the population; 2-sided test; α = .05; and β = .8. A sample of 58 patients per group was required to estimate a difference in time to initial administration of analgesic of 30 minutes and in LOS from triage to disposition in the UC center.…”
Section: Methodsmentioning
confidence: 99%